PEMANFAATAN METODE IQRO SEBAGAI PEMBELAJARAN BACA TULIS HURUF HIJIYAH BAGI ANAK SEBAGAI UPAYA PEMBERANTASAN BUTA AKSARA HURUF HIJAIYAH DI DESA PELAWI SELATAN, KECAMATAN BABALAN, KABUPATEN LANGKAT - Abu Bakar; Sulaiman Tamba; Habibullah Habibullah; Sri Hastuti Br Saragih; Teddy Hardiansyah (Jurnal Pengabdian Mitra Masyarakat, 2022)
Qur'an is the guide of Muslims in the world and is obliged for Muslims to learn to read the Qur'an properly and correctly in accordance with the rules of tajwid science. Students should have read the Qur'an since childhood because there are so many who cannot read the Qur'an. The ability to read the Qur'an is very important for Muslims, because it is a guide for their lives. South Pelawi Village is a partner village of UISU which is known as an area where almost 90% of the people are Muslims. However, there are still many people, both children and adults, who do not understand and are fluent in reading the Qur'an. One of the learnings of reading the Qur'an is the IQRO method, the IQRO method is a method of reading the Qur'an that emphasizes directly on reading practice. As for the Iqra guidebook consisting of 6 Volumes starting from a simple level, step by step to a perfect level, this method is very suitable to be applied for early childhood (children aged 3 years).  This service activity is one of the derivatives of the 2022 UISU KKNT work program which will be held on July 12 – August 19, 2022. This activity was carried out as many as 12 meetings from July 18 to August 10, 2022. From the activities that have been carried out, it was found that residents learned to experience an increase in the ability to read and write the Qur'an. This proves the effectiveness of the IQRO method used in the eradication of Qur'anic illiteracy. Because only with approximately 1 month with an effective period of learning 12 meetings, 87% have fluently read the Qur'an. Only 13% of citizens are learning that has not been smooth.